2018
DOI: 10.1016/j.cell.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Mediated Programmable 3D Genome Positioning and Nuclear Organization

Abstract: SUMMARY Programmable control of spatial genome organization is a powerful approach for studying how nuclear structure affects gene regulation and cellular function. Here, we develop a versatile CRISPR-genome organization (CRISPR-GO) system that can efficiently control the spatial positioning of genomic loci relative to specific nuclear compartments, including the nuclear periphery, Cajal bodies, and promyelocytic leukemia (PML) bodies. CRISPR-GO is chemically inducible and reversible, enabling interrogation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(124 citation statements)
references
References 48 publications
2
113
1
Order By: Relevance
“…ChromSTEM platform for analysis of chromatin organization 3D chromatin organization governs gene transcription by controlling genome connectivity, DNA accessibility, and transcriptional heterogeneity 26,27,28 . Emerging evidence shows that the proper positioning of the chromatin within the nucleus also plays an indispensable role in maintaining normal transcriptional function 10,29 . Utilizing the ChromSTEM platform, one can obtain quantitative information on the native 3D chromatin architecture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ChromSTEM platform for analysis of chromatin organization 3D chromatin organization governs gene transcription by controlling genome connectivity, DNA accessibility, and transcriptional heterogeneity 26,27,28 . Emerging evidence shows that the proper positioning of the chromatin within the nucleus also plays an indispensable role in maintaining normal transcriptional function 10,29 . Utilizing the ChromSTEM platform, one can obtain quantitative information on the native 3D chromatin architecture.…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of gene transcription is essential in sustaining normal cell function, controlling cell differentiation and determining cell fate, and transcriptional alterations have been implicated in a variety of diseases including cancer and cardiovascular, developmental, neurological, and autoimmune disorders 1,2,3 . While early studies, which focused on the molecular mechanisms of transcriptional regulation based on a linear model of genome organization, provided significant knowledge of the genome regulation, they also demonstrated the substantial limitations of this approximation 4,5,6,7,8,9,10 . Recent studies have unambiguously shown that genes can interact with multiple distal elements within distances up to several Mb away, suggesting a machinery of transcriptional regulation based on the three-dimensional (3D) chromatin structure 11,12,13,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Cells can be recovered after LiveFISH analysis for culture, sequencing, and functional characterization (Supplementary Figure 7). The human genome contains many repetitive sequence clusters that are highly abundant and adjacent (within 100kb) to the majority (>60%) of encoding genes, which can serve as robust chromosomal imaging regions (43). Given the targeting-flexibility of LiveFISH, our approach offers a new way to studying dynamics of translocations induced by gene editing at various endogenous genomic locations.…”
Section: Discussionmentioning
confidence: 99%
“…Given the targeting-flexibility of LiveFISH, our approach offers a new way to studying dynamics of translocations induced by gene editing at various endogenous genomic locations. The possibility of combining CRISPR LiveFISH with gene editing and other manipulation techniques (e.g., CRISPRi/a, epigenetic modification, CRISPR-GO) should further expand our capability to study the spatiotemporal dynamics of genome organization and rearrangements (16,20,(43)(44)(45)(46)(47). Figure 5D for raw sanger sequencing data.…”
Section: Discussionmentioning
confidence: 99%
“…These methods are applied to fixed cells. On the other hand, CRISPR-based imaging provides a versatile and powerful tool to track chromatin topology in live cells in real time [10][11][12] .…”
mentioning
confidence: 99%